Malika : warrior queen. Volume 2 - Okupe, Roye (Dark Horse Books, 2021)
"After years of moving in the shadows, Malika is forced out of hiding by the Olon Jin--ancient sorcerers imprisoned for centuries because of their obsession with dark magic. In their sights is the Fire and Frost stone, a relic that holds the combined power of two legendary dragons. On her journey to Egypt to retrieve the stone, Malika uncovers a sinister plot that predates her own five-hundred-year-old legend as Warrior Queen and threatens to end humanity."--Amazon